A Focal Organization Perspective Toward Interorganizational Collaboration: The Case of the HIV/AIDS Epidemic in India. Issue 9 (October 2019) - Escobar, Luis F.; Deshpande, Sameer
We propose, from a focal organization's perspective, a holistic framework for an interorganizational collaboration (IOC) that integrates the resource dependence theory and the triangular alignment perspective to account for the impact external factors such as international donors and internal factors such as the focal organization's competencies have on the IOC's antecedents, process, and outcomes. We base our arguments on the case of the National AIDS Control Organisation (NACO) that collaborated with various international and domestic partners to effectively reduce the incidence of HIV/AIDS in India.